Duhovna oskrba bolnikov - Zavrl, Bor (Retrospektive, 2025)
In the Ljubljana suburb of Vodmat or Šentpeter, a »health city« was formed at the end of the 19th century. The most important hospitals and health institutions were concentrated here. People received help and care in cases of injury and illness. In addition to doctors, members of charitable religious orders - nuns - dominated the service and care of patients. They needed a space, a chapel, to perform their religious duties. In the past, they knew that a sick person, in addition to caring for their physical needs, also needed care for their spiritual needs. In those days, religion and its expression were everyday life and the most common form of expressing human spirituality. For both reasons, spaces dedicated to spirituality - chapels were arranged in health institutions. In our area, the Catholic faith prevailed, and so Catholic chapels dominated in these institutions. The largest space/ facility for spiritual care in this health city was the hospital church, dedicated to the Holy Cross. This year marks 130 years since the construction of this church, 77 years since it has been out of use and 28 years since it was finally demolished. It served its primary purpose for 53 years. Chapels were located in numerous health institutions until the liberation in 1945. The chapel was owned by the predecessor of the Oncology Institute, the Children's Hospital, the Mental Hospital, the Women's Hospital... Until the change of government and social order, the spiritual care of patients, chapels and the named church were a permanent feature of health institutions. Later, this was no longer desirable. The premises where the chapels were were converted for other purposes, the church was given another purpose, until it disappeared. After independence, however, the spiritual care of patients and chapels regained their place in health institutions. The article will present facilities for spiritual care, Catholic faith in the area of the Ljubljana Hospital or. today's University Medical Center Ljubljana.
Keywords: bolnišnica; care; cerkev; chapel; church; history; hospital; kapela; oskrba; zgodovina